2020
DOI: 10.3390/ijerph17020621
|View full text |Cite
|
Sign up to set email alerts
|

Health and Sustainability in Public Meals—An Explorative Review

Abstract: The world is facing a number of challenges related to food consumption. These are, on the one hand, health effects and, on the other hand, the environmental impact of food production. Radical changes are needed to achieve a sustainable and healthy food production and consumption. Public and institutional meals play a vital role in promoting health and sustainability, since they are responsible for a significant part of food consumption, as well as their “normative influence” on peoples’ food habits. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In line with other studies where meals in public institutions are identified as an arena for health promotion as well as a way to achieve social equality (Höijer et al, 2020;Illøkken et al, 2021), our study confirmed that food practices in kindergartens could contribute to the sociocultural sustainably through food in ECEC. Building on the evidence that children's eating patterns and food preferences are established early in life (Birch & Fisher, 1998), and seeing as many eating behaviors (such as food variety and intake) are consistent over time (Nicklaus & Remy, 2013), the findings of our study suggest that kindergarten has the potential to facilitate an environment that helps children to develop long-lasting habits and skills, as well as good relationship with food.…”
Section: Children's Agency For Sustainable Changesupporting
confidence: 90%
“…In line with other studies where meals in public institutions are identified as an arena for health promotion as well as a way to achieve social equality (Höijer et al, 2020;Illøkken et al, 2021), our study confirmed that food practices in kindergartens could contribute to the sociocultural sustainably through food in ECEC. Building on the evidence that children's eating patterns and food preferences are established early in life (Birch & Fisher, 1998), and seeing as many eating behaviors (such as food variety and intake) are consistent over time (Nicklaus & Remy, 2013), the findings of our study suggest that kindergarten has the potential to facilitate an environment that helps children to develop long-lasting habits and skills, as well as good relationship with food.…”
Section: Children's Agency For Sustainable Changesupporting
confidence: 90%
“…School feeding programs are considered a target for sustainability actions. Indeed, a recent explorative review [ 15 ] claimed that schools and hospitals are the most dominant arenas where both health and sustainability have been addressed in order to reach a more holistic perspective on food consumption of public meals. In Spain, a feeding program was designed to develop a one-month healthy and sustainable lunch plan for primary school children [ 11 ] that provides a reduction of 13–24% of GHGE and 10–15% of the cost while maintaining the nutritional quality.…”
Section: Introductionmentioning
confidence: 99%
“…Public meals aimed at relieving economically poor strata from stigmatised food aid, primarily through ‘the modern school lunch’ (Gullberg, 2006). Public meals have now become integral to Swedish welfare politics (Sporre et al, 2017); more than three million meals are served daily in Swedish preschools and schools, hospitals and care institutions (Höijer et al, 2020). Yet, scholars continue to illuminate how the Swedish welfare system is incomplete (Inghe and Inghe, 1968; Swärd, 2017).…”
Section: Food Practices Of Folkkök In Sweden: From Altruistic To Anar...mentioning
confidence: 99%